2018
DOI: 10.1080/19476337.2017.1406407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of traditional dehydration processing of pepper jalapeno rayado (Capsicum annuum) on secondary metabolites with antioxidant activity

Abstract: Jalapeno rayado peppers (Capsicum annuum) are usually subjected to a traditional smoke-dehydration process using Quercus sp. This treatment provides peppers with their characteristic functional attributes. To differentiate the production of antioxidant metabolites during the dehydrationsmoking process, this process was compared with convective dehydration, both at 60°C. A higher antioxidant activity in smoke-dried pepper was observed due to the increase in concentration of phenolic compounds, flavonoids and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 27 publications
1
13
2
10
Order By: Relevance
“…[46]. Antioxidant capacity was 15% of that measured in C. frutescens [45] and 19% of the highest value reported for red dry fruits of C. annuum [44]. Values were similar to those reported for pepper, although cacho de cabra was 7% over the level reported for an unspecified Chilean cultivar [47].…”
Section: Chemical Analysissupporting
confidence: 61%
See 2 more Smart Citations
“…[46]. Antioxidant capacity was 15% of that measured in C. frutescens [45] and 19% of the highest value reported for red dry fruits of C. annuum [44]. Values were similar to those reported for pepper, although cacho de cabra was 7% over the level reported for an unspecified Chilean cultivar [47].…”
Section: Chemical Analysissupporting
confidence: 61%
“…Total phenolic content in chileno negro was in the upper end of the range for 51 Brazilian accessions of Capsicum species, while in cacho de cabra, it was 32% over the highest value [43]. Cacho de cabra represented 90% of the value measured in a Mexican type of C. annuum (jalapeño) [44]. Comparable values of total phenolics to those found in cacho de cabra were reported in a Japanese cultivar of C. frutescents L. [45].…”
Section: Chemical Analysismentioning
confidence: 66%
See 1 more Smart Citation
“…With respect to the variation in the carotenoid content of the dried jalapeño chili peppers, Daood et al (2006) demonstrated that the loss of carotenoids in red peppers increased as the drying temperature was raised in increments of 10 °C, and boiling and grilling have been reported to consistently decrease the concentrations of all forms of carotenoids (Cervantes-Paz et al, 2014). Other authors have indicated that convective dehydration and smoke drying decrease the carotenoid content by approximately 40% in relation to that of fresh red chili peppers (Campos-Hernández et al, 2018). According to some authors, heat exerts a significant effect on the total carotenoid content of dried mango, with the highest levels of carotenoids being retained in lyophilized samples; the obtained results are in accordance with previous reports indicating a declining trend in carotenoid content values when driers are operated at higher temperatures (Sogi et al, 2015).…”
Section: Effect Of the Drying Process On The Nutraceutical Compounds ...mentioning
confidence: 97%
“…The measuring of the surface colour of fresh and dried samples was carried out using the colorimeter (model PCE-CSM 1) based on three-color coordinates, i.e., L*, a* and b*. The L value signifies the lightness (100 for white and 0 for black), a represents redness (-80 for green and 100 for red) while b signifies the change from blueness to yellowness (-80 for blue and 70 for yellow) [6]. Results are the average of three independent experiments performed in triplicate and color difference (ΔE) was calculated.…”
Section: Surface Color Measurementmentioning
confidence: 99%